METAPHORS FOR EVANGELISM. Issue 3 (July 2019) - Threlfall-Holmes, Miranda
Abstract : This paper identifies and critiques four key metaphors that have been dominant in shaping the Christian churches' understanding and practice of evangelism historically, and which are still powerful today: rescue, battle, healing and teaching. The extent to which these metaphors are helpful in liberal evangelism is discussed. Finally, some alternative metaphors – play, midwifery, storytelling – are proposed.